Research on the Path and Strategy of Enterprise Digital Transformation in the Era of Digital Economy - Li, Qingrui (International Journal of Global Economics and Management, 2025)
This research explores the strategic pathways for successful enterprise digital transformation in the digital economy. By analyzing key elements and stages, the study develops a tailored framework for effective digital transformation strategies, specific to industry sectors and enterprise characteristics. It examines the impact of digital technology adoption on business models, operational efficiency, and customer engagement, alongside the challenges and opportunities in managing organizational change. The findings emphasize a holistic approach integrating strategic planning, technology adoption, organizational change management, and ecosystem collaboration. This research contributes to the digital transformation discourse by identifying best practices and success factors for enterprises navigating the digital economy.